Characterizing environmental stress responses of aposymbiotic Astrangia poculata to divergent thermal challenges. Issue 20 (25th August 2021) - Wuitchik, Daniel M.; Almanzar, Adeline; Benson, Brooke E.; Brennan, Sara; Chavez, Juan D.; Liesegang, Mary B.; Reavis, Jennifer L.; Reyes, Christopher L.; Schniedewind, Mikaela K.; Trumble, Isabela F.; Davies, Sarah W.
Abstract: Anthropogenic climate change threatens corals globally and both high and low temperatures are known to induce coral bleaching. However, coral stress responses across wide thermal breadths remain understudied. Disentangling the role of symbiosis on the stress response in obligately symbiotic corals is challenging because this response is inherently coupled with nutritional stress. Here, we leverage aposymbiotic colonies of the facultatively symbiotic coral, Astrangia poculata, which lives naturally with and without its algal symbionts, to examine how broad thermal challenges influence coral hosts in the absence of symbiosis. A . poculata were collected from their northern range limit and thermally challenged in two independent 16‐day common garden experiments (heat and cold challenge) and behavioural responses to food stimuli and genome‐wide gene expression profiling (TagSeq) were performed. Both thermal challenges elicited significant reductions in polyp extension. However, there were five times as many differentially expressed genes (DEGs) under cold challenge compared to heat challenge. Despite an overall stronger response to cold challenge, there was significant overlap in DEGs between thermal challenges. We contrasted these responses to a previously identified module of genes associated with the environmental stress response (ESR) in tropical reef‐building corals. Cold challenged corals exhibited a pattern consistent with more severe stressors while the heat challenge response was consistent with lower intensity stressors. Given that these responses were observed in aposymbiotic colonies, many genes previously implicated in ESRs in tropical symbiotic species may represent the coral host's stress response in or out of symbiosis.